Determinan Faktor-Faktor Capability sebagai Perspektif Fraud Diamond terhadap Kecurangan Laporan Keuangan - Putri, Yasinta Earlyda; Elly Suryani (Politeknik Ganesha Medan, 2024)
Financial statement fraud is defined as deliberately not following the accepted accounting principles when reporting financial information, which leads to significant omissions or distortions of the facts. The purpose of this study is to determine the effect of capability in detecting fraudulent financial statements. Fraudulent financial statements can occur when a company intentionally violates accounting principles or ignores applicable financial reporting standards. Fraud diamond is one of fraud risk factor, one of which is capability. Many frauds, especially some of the multibillion-dollar ones, would not have occurred without the right person with the right capabilities in place. In this study, capabilities as measured by CEO prestige power, CEO education, CEO experience, CEO horizon, CEO founder, CEO expert power, CEO age similarity, and CEO number executive. The type of data used in this study is secondary data in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. Sampling method by purposive sampling, obtained as many as 114 companies as samples. The data analysis method used logistics regression. The results of this study show that CEO age similarity and CEO number executive has a positive impact on fraudulent financial statements, meanwhile the other variables have no impact of fraudulent financial statements.